2021
DOI: 10.1007/s12975-021-00937-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Machine Learning Models to Predict Probabilities and Types of Stroke at Prehospital Stage: the Japan Urgent Stroke Triage Score Using Machine Learning (JUST-ML)

Abstract: In conjunction with recent advancements in machine learning (ML), such technologies have been applied in various fields owing to their high predictive performance. We tried to develop prehospital stroke scale with ML. We conducted multi-center retrospective and prospective cohort study. The training cohort had eight centers in Japan from June 2015 to March 2018, and the test cohort had 13 centers from April 2019 to March 2020. We use the three different ML algorithms (logistic regression, random forests, XGBoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The overall DTA of the five prospective studies and 104,397 scans was estimated using a univariate meta-analysis with a pooled sensitivity was 0.886 (95% CI 0.613–0.975, I 2 = 100%) ( Fig. 7 ) [ 24 , 29 , 33 , 40 , 44 ]. The pooled specificity was 0.967 (95% CI 0.937–0.983, I 2 = 100%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall DTA of the five prospective studies and 104,397 scans was estimated using a univariate meta-analysis with a pooled sensitivity was 0.886 (95% CI 0.613–0.975, I 2 = 100%) ( Fig. 7 ) [ 24 , 29 , 33 , 40 , 44 ]. The pooled specificity was 0.967 (95% CI 0.937–0.983, I 2 = 100%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the high AUC of the included trials could not correctly represent the performance of the algorithm's therapeutic benefit [ 54 ]. Initially, the range of AUC among studies was 0.608 to 1 that Neural Networks (NNs) learning such as CNN, ResNet, and RNN had a higher rate from other ML algorithms [ 20 , 21 , 23 , 24 , 26 29 , 31 , 33 , 37 39 , 43 , 44 , 46 , 49 ]. In other words, this result suggested that NNs algorithms in the big data can improve the rate of AUC which it is a useful way to detect a good model and positive and negative target classes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more neoteric advancements of on scene CCDS is predicting end diagnosis to expedite specialist care or to instigate earlier treatment. As an example, The Japanese Urgent Stroke Triage Score using Machine Learning (JUST-ML) predicted a major neurological event such as a large vessel occlusion, subarachnoid haemorrhage, intracranial haemorrhage or cerebral infarction better than any other available model [ 32 ]. The benefit of predicting a major neurological event in the pre-hospital phase of care is that it can steer transport destination decisions to ensure the right patients go to a stroke unit for specialist care.…”
Section: Discussionmentioning
confidence: 99%
“…The random forest (RF) classifier is a ML method that generates high accuracy in the data analysis of various diseases, such as cardiovascular disease [ 21 ], stroke [ 22 ], cataracts [ 23 ], and ovarian cancer [ 24 ], because it can consider interactions between variables and is not affected by possible outliers. The RF classifier is one of the class identification methods in which data and explanatory variables are randomly divided to create multiple decision trees, and the final classification is achieved by the majority vote [ 25 ].…”
Section: Introductionmentioning
confidence: 99%